Factors affecting the performance of sea transportation and Port Infrastructure Development and its implications for the economic growth of the maritime sector in Indonesia - Sugeng Siswanto; Heru Subiyantoro; Cicih Ratnasih (PT. Anagata Sembagi Education, 2025)
Indonesia, as an archipelagic country, has a high dependence on maritime transportation and port infrastructure to support economic and trade activities. However, the performance of maritime transportation and the development of port infrastructure still face various challenges, including low operational efficiency, limited investment, and unsynchronized regulations. This study aims to analyze the factors affecting maritime transportation performance and port infrastructure development in Indonesia using the Fixed Effect Model (FEM) approach and the Least Square Dummy Variable (LSDV) method. The data used covers the period from 2011 to 2023, focusing on five major ports in Indonesia: Tanjung Priok, Tanjung Perak, Belawan, Makassar, and Balikpapan. The research findings indicate that port operational efficiency, maritime sector investment, and technology adoption have the most significant influence on maritime transportation performance. Meanwhile, port infrastructure development is primarily influenced by maritime sector investment and inter-port connectivity. Additionally, improvements in maritime transportation performance and port infrastructure have been proven to positively impact maritime economic growth. Therefore, strategic policies focusing on sustainable investment, operational efficiency enhancement, and technology integration are essential to strengthen the competitiveness of Indonesia’s maritime sector at the global level.